Use of Farnesyl Transferase Inhibitors in an Ageing Model in Drosophila - Annely Brandt; Roman Petrovsky; Maria Kriebel; Jörg Großhans (Journal of Developmental Biology, 2023)
The presence of farnesylated proteins at the inner nuclear membrane (INM), such as the Lamins or Kugelkern in Drosophila, leads to specific changes in the nuclear morphology and accelerated ageing on the organismal level reminiscent of the Hutchinson–Gilford progeria syndrome (HGPS). Farnesyl transferase inhibitors (FTIs) can suppress the phenotypes of the nuclear morphology in cultured fibroblasts from HGPS patients and cultured cells overexpressing farnesylated INM proteins. Similarly, FTIs have been reported to suppress the shortened lifespan in model organisms. Here, we report an experimental system combining cell culture and Drosophila flies for testing the activity of substances on the HGPS-like nuclear morphology and lifespan, with FTIs as an experimental example. Consistent with previous reports, we show that FTIs were able to ameliorate the nuclear phenotypes induced by the farnesylated nuclear proteins Progerin, Kugelkern, or truncated Lamin B in cultured cells. The subsequent validation in Drosophila lifespan assays demonstrated the applicability of the experimental system: treating adult Drosophila with the FTI ABT-100 reversed the nuclear phenotypes and extended the lifespan of experimentally induced short-lived flies. Since kugelkern-expressing flies have a significantly shorter average lifespan, half the time is needed for testing substances in the lifespan assay.